Հայոց ցեղասպանության մասին ժողովրդական երգերը երաժշտա-բանաստեղծական հատկանիշների տեսանկյունով - Անահիտ Բաղդասարյան (ՀՀ ԳԱՍ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
Геноцид армян, учиненный властями Турции в конце 19-го, начале 20-го веков, и особенно в период Первой мировой войны, по оценке ученых, одна из величайших трагедий в истории человечества, нашел свое отражение во всех областях национального искусства-архитектуре, скульптуре, живописи, литературе, театре, кино. В этом ряду важное место имеет армянская музыка. С течением времени было создано большое количество народных, ашугских песен, композиторских произведений. The Armenian Genocide organized by Turkish state power, at the end of 19th century, beginning of 20th century, and particularly in period of First World War, was reflected in all fields of the national art-archirecture, sculpture, painting, literature, theatre, cinema. This theme has an important place in Armenian music. During the years there were created many folk and ashug songs, various creations of composers, appeared new genres, forms of rendering, which with few exceptions were not sufficiently taken into the consideration in musicological literature.
Keywords: Պատմագրություն; Հայոց ցեղասպանություն (1915)